Determinan Kejadian Hipertensi Pada Pasien Pra Lansia di Poli Penyakit Dalam RS.TK II.DR.R.Hardjanto Balikpapan Kalimantan Timur 2025 - Sandan, Meli; Ulfa, Laila; Aprilia, Yuna Trisuci (Jurnal Untuk Masyarakat Sehat (JUKMAS), 2025)
Hypertension is a major health concern among pre-elderly (ages 45–59) due to physiological changes and unhealthy lifestyles. In Balikpapan, it ranks second among diseases at RS TK.II DR. R. Hardjanto. This study aimed to identify determinants of hypertension in this group. The research design was cross-sectional with a quantitative approach involving 96 respondents. Data were analyzed using univariate, bivariate (chi-square), and multivariate (logistic regression) tests. The results revealed significant associations with education p=0,004, occupation p=0,001, family history p=0,062, salt intake p=0,001, obesity p=0,000, physical activity p=0,011, and stress p=0,013. The three dominant factors were family history (OR = 60.809), high salt intake (OR = 3.696), and obesity (OR = 5.357). Hypertension prevention should focus on lifestyle modifications and health education.